Emergency Medicine Gender‐specific Education. (December 2014) - Ashurst, John V.; McGregor, Alyson J.; Safdar, Basmah; Weaver, Kevin R.; Quinn, Shawn M.; Rosenau, Alex M.; Goyke, Terrence E.; Roth, Kevin R.; Greenberg, Marna R.; Cone, David C.
Abstract The 2014 Academic Emergency Medicine consensus conference has taken the first step in identifying gender‐specific care as an area of importance to both emergency medicine (EM) and research. To improve patient care, we need to address educational gaps in this area concurrent with research gaps. In this article, the authors highlight the need for sex‐ and gender‐specific education in EM and propose guidelines for medical student, resident, and faculty education. Specific examples of incorporating this content into grand rounds, simulation, bedside teaching, and journal club sessions are reviewed. Future challenges and strategies to fill the gaps in the current education model are also described.